2023
DOI: 10.1071/wr22078
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structure facilitates coexistence of native and invasive mesopredators in an Australian tropical savanna

Abstract: Context. The introduction of the cat (Felis catus) to Australia has been a key driver of the decline and extinction of the continent's endemic mammals. Currently, there is no clear long-term solution to controlling feral populations of cats at a landscape scale. As such, understanding how environmental conditions and habitat attributes can mediate the coexistence between introduced predators and native mammals can improve management outcomes for threatened species. Aim. We sought to compare the differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
0
1
0
Order By: Relevance
“…For example, previous studies conducted in the savannas of the Kimberley and Cape York Peninsula regions by McGregor et al (2014McGregor et al ( , 2015 demonstrated that feral cats exhibit improved hunting efficiency in grassland and recently burnt habitats. Similarly, Trewella et al (2023) found that habitat use by feral cats was most frequent in areas with high fire frequencies and low tree basal area. It is plausible, therefore, that mature Acacia shrubland and eucalypt woodland (>3 years post fire) limit the hunting efficiency of feral cats by providing complex vegetation cover for Ngarlgumirdi.…”
Section: How Does Fire Influence the Distribution Of Feral Cats On Th...mentioning
confidence: 90%
“…For example, previous studies conducted in the savannas of the Kimberley and Cape York Peninsula regions by McGregor et al (2014McGregor et al ( , 2015 demonstrated that feral cats exhibit improved hunting efficiency in grassland and recently burnt habitats. Similarly, Trewella et al (2023) found that habitat use by feral cats was most frequent in areas with high fire frequencies and low tree basal area. It is plausible, therefore, that mature Acacia shrubland and eucalypt woodland (>3 years post fire) limit the hunting efficiency of feral cats by providing complex vegetation cover for Ngarlgumirdi.…”
Section: How Does Fire Influence the Distribution Of Feral Cats On Th...mentioning
confidence: 90%
“…Camera‐trap models used included Reconyx HC550 (white flash), Reconyx HC600 (infrared flash), Reconyx PC900, Scoutguard 560DF (dual flash), and Scoutguard 565F (white flash). Cameras were mounted to a tree or post either 1 or 1.5 m above the ground and oriented vertically (facing downward), so as to capture unique spot patterning located on the dorsal surface of animals (see Diete et al., 2017; Indigo et al., 2023; Moore et al., 2020; Trewella et al., 2023). All cameras were baited (fish, peanut butter, or sesame oil) and left active for between 2 and 150 days at a time.…”
Section: Methodsmentioning
confidence: 99%